2019
DOI: 10.1002/ijc.32379
|View full text |Cite
|
Sign up to set email alerts
|

Neddylation inhibition upregulates PD‐L1 expression and enhances the efficacy of immune checkpoint blockade in glioblastoma

Abstract: Pevonedistat (MLN4924), a specific NEDD8‐activating enzyme inhibitor, has been considered as a promising treatment for glioblastoma, which is currently in Phase I/II clinical trials. On the other hand, inhibition of neddylation pathway substantially upregulates the expression of T cell negative regulator programmed death‐ligand 1 (PD‐L1), which might account for the potential resistance via evasion of immune surveillance checkpoints. Whether administration of anti‐PD‐L1 enhances the efficacy of pevonedistat th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 43 publications
2
38
0
Order By: Relevance
“…The high expression of PD-L1 protein levels is observed in different types of cancers, which promotes cancer cell immune escape 5,7 . The expression of PD-L1 in cancer cells is regulated by multiple signaling pathways, including NFκB, MAPK, mTOR, STAT, and c-Myc 8,9 , while PD-L1 protein undergoes degradation in proteasomes or lysosomes by multiple pathways [10][11][12][13][14][15][16] , leading to increased effectiveness of cancer immunotherapy (Figs. 1 and 2 and Tables 1 and 2).…”
Section: Introductionmentioning
confidence: 99%
“…The high expression of PD-L1 protein levels is observed in different types of cancers, which promotes cancer cell immune escape 5,7 . The expression of PD-L1 in cancer cells is regulated by multiple signaling pathways, including NFκB, MAPK, mTOR, STAT, and c-Myc 8,9 , while PD-L1 protein undergoes degradation in proteasomes or lysosomes by multiple pathways [10][11][12][13][14][15][16] , leading to increased effectiveness of cancer immunotherapy (Figs. 1 and 2 and Tables 1 and 2).…”
Section: Introductionmentioning
confidence: 99%
“…43 Neddylation inactivation also upregulates PD-L1 expression on glioblastoma cell lines by stabilization of c-Myc. 54 Adaptor protein Shc is another target for neddylation, which facilitating the formation of the ZAP70-Shc-Grb2 complex and downstream Erk activation. 48 NEDD8 modification of Itch, leading to degradation of FoxO1, promotes Tfh cell differentiation.…”
Section: Neddylation and Other Signalsmentioning
confidence: 99%
“…57 Another study indicated that neddylation inhibition significantly enhances Cullin-1/c-Mycmodulated PD-L1 expression in glioblastoma cancer cell lines, resulting in T-cell exhaustion and attenuated T-cell killing. 54 Besides of solid tumors, unique effects of neddylation inhibition on lymphoid malignancies have been discussed recently. NAE inhibition treated T cells derived from patients with chronic lymphocytic leukemia exert markedly differential expression of NF-κB-regulated genes and downregulated of interleukin-2 signaling during T-cell activation.…”
Section: Neddylation In Cancermentioning
confidence: 99%
See 2 more Smart Citations